Acceleration profile of high-impact movements during young football games: a cross-sectional study involving healthy children - Sasaki, S.; Nagano, Y.; Suganuma, Y.; Koyama, T.; Ichikawa, H. (Sports Biomechanics, 2024)
Repetitive high-impact movements cause growth-related injuries in children. This study aimed to identify which movements during junior football games require >6G and >8G acceleration and the frequency at which they occur. Additionally, we compared the components of acceleration among movements with >8G resultant acceleration. Eleven young male footballers (10.7±0.4years) played 8-a-side games while wearing a tri-axial accelerometer on their upper back. The number and frequency of the movements that generated >6G and >8G were calculated, and each directive acceleration of the top five items was compared using two-way ANOVA to examine the effect of movements. The frequency of movements that generated >6G and >8G acceleration during junior football games was 8.70 case/min and 2.62 case/min, respectively. The top five >8G movements were braking and pre-braking in shuffle, slowdown, stop, and run/jog items. The vertical acceleration was significantly greater during braking in shuffle than during slowdown, stop, and run/jog and also greater during stop and pre-braking in shuffle than during run/jog movement. This pilot study suggests that decelerated movements mainly provoked high-impact situations and may be key actions for preventing overuse injury in young footballers.